Association of 25-hydroxyvitamin D with sex hormones and body composition in Chinese older adults - Miao, Xinyu; Ma, Cong; Gu, Zhaoyan; Yan, Shuangtong; Gong, Yanping; Xu, Guogang (Frontiers in Endocrinology, 2025)
BackgroundEvidence from several studies suggests that vitamin D deficiency is associated with reduced testosterone levels. However, evidence regarding the relationships between serum 25-hydroxyvitamin D [25-(OH)D] and sex hormones remains inconsistent. This study focuses on older adults, aiming to investigate the associations of 25-(OH)D with sex hormones and body composition.MethodsA cross-sectional study was conducted, enrolling 2472 older adults (1406 males; 1066 females) aged 60 years or older who underwent routine health examinations at the Chinese PLA General Hospital in 2018 and 2019. Anthropometric measurements, biochemical characteristics, sex hormones, body composition, and chronic comorbidities were compared after stratification by 25-(OH)D levels. Multiple linear regression and logistic regression analyses were performed to explore the relationships of 25-(OH)D status with sex hormones and body composition.ResultsAmong the older adults in this study, the proportion of those with insufficient/deficient vitamin D was 87.4% (1229/1406) in males and 91.8% (979/1066) in females. By 25-(OH)D stratification (from sufficiency to deficiency), males showed increasing trends in body mass index (BMI), waist circumference (WC), body fat percentage, muscle mass and basic metabolic rate, smoking rate, triglycerides (TG), parathyroid hormone (PTH), and prolactin (PRL), along with decreasing trends in albumin (Alb), serum calcium (Ca), high-density lipoprotein cholesterol (HDL-C), serum creatinine (Cr), aspartate aminotransferase (AST) and testosterone; females exhibited similar trends, with additional decreases in hemoglobin (Hb), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) (all P<0.05). In males, a 10 ng/ml decrease in 25-(OH)D was associated with a -0.95 (-1.46, -0.45) nmol/L change in T levels and a 26% higher risk of hypogonadism (defined as total testosterone <12 nmol/L), though these associations disappeared after adjusting for age and BMI. For every 10 ng/ml decrease in 25-(OH)D, body fat percentage, muscle mass, and basal metabolic rate increased in both older males and females. After adjusting for confounding factors, only body fat percentage increased by 0.30 (0.00, 0.59) % in older males.ConclusionIn elderly men, 25-(OH)D levels correlated positively with total testosterone, but this correlation may be BMI-dependent. Additionally, as 25-(OH)D levels decreased, body fat percentage increased in this group, suggesting a potential mediating role of increased BMI/adiposity in the vitamin D-testosterone relationship.